A Structuralist Study of the Wayang Suket Puspasarira Malang - Siti Zurinani (Jurusan Sastra Indonesia, 2017)
Wayang is one of the art forms of Javanese society which has been patented as a cultural heritage, specifically as a Masterpiece of the Oral and Intangible Heritage of Humanity, in 2003. As a cultural heritage, wayang contains various elements of art such as visual arts, sound arts, and drama. In addition, wayang also becomes a facility for rituals, amusement, and aesthetic presentation. Moreover, wayang has been used as a “reference for a better life, because it portrays the eternal messages of humanity”. The messages develop an awareness of the audience about good and bad things in life. This research describes the structure and representation of Javanese life philosophy in wayang puspasarira. Through this research, wayang puspasarira has a symbolic structure of the moral and cultural values of Javanese society.